Topical Diltiazem Vs. Travoprost in Reducing Intraocular Pressure in Ocular Hypertensive / Glaucomatous Rabbits - Zulfiqar Ali, Saadat Ullah Khan, Zulfiqar uddin Syed (Pakistan Journal of Ophthalmology, 2021)
Purpose: To demonstrate the Intraocular Pressure (IOP) lowering effect of topical Diltiazem (calcium channel blocker) in comparison to Travoprost (antiglaucoma drug). Material and Methods: The study was conducted on 50 healthy rabbits of local strain, weighing 1500 to 2000 grams. They were kept at the animal house of Department of Pharmacology, Khyber Medical College Peshawar. Effect of drugs was studied on both eyes of conscious rabbits. Rabbits were divided into four groups i.e. A, B, C and D. Rabbits of group A, B and C were made ocular hypertensive / glaucomatous by injecting weekly sub conjunctival betamethasone suspension. The iatrogenic glaucoma of group “A” animals were treated with topical Diltiazem and group B with topical Travoprost drops. Group C served as ocular hypertensive control. It received only artificial tears during the research period. Group D rabbits were used as normotensive control. They were neither induced for glaucoma nor did they receive any treatment during the research period. Results: Our study revealed that there was 19% (5.00 + 0.25 mm Hg) drop in Intra Ocular Pressure with topical Diltiazem. Its onset of action was quick and duration of action prolonged. Whereas topical Travoprost reduced IOP by 15% (4.00 + 0.25 mm Hg). Topical Diltiazem was found consistent in its intraocular pressure lowering effect as compared to Travoprost. Conclusion: Topical Diltiazem can be used as an alternative anti glaucoma drug in future if found safe in human trials. Key words: Glaucoma, Ocular hypertension, Betamethasone suspension, Calcium Channel Blockers (CCB), Intraocular Pressure (IOP).